Coordination-driven hierarchically structured composites with N-CNTs-grafted graphene-confined ultra-small Co nanoparticles as effective oxygen electrocatalyst in rechargeable Zn-air battery. Issue 21 (1st November 2021) - Shen, Mengxia; Gao, Kun; Duan, Chao; Hu, Weihang; Ding, Shujiang; Yang, Guihua; Ni, Yonghao
Abstract: Rational design and fabrication of optimal reversible oxygen electrocatalysts are essential yet still remain great challenges for rechargeable metal-air batteries. Supramolecular coordination polymer-derived strategy for transition metal–nitrogen–doped carbon (M–N/C, M = Co, Fe, etc.) composites catalysts has been deemed promising in preserving rich M–Nx coordination modes and enhancing their intrinsic activities. However, the closely packed and nonporous characteristics of coordination polymer usually lead to the serious agglomeration of metallic nanoparticles and lack of porous channels after pyrolysis, impacting the abundance and accessibility of the exposed active sites during electrocatalysis. In this work, we put forward a new tactic to obtain ultra-small Co nanoparticles confined within N-doped carbon nanotubes grafted to reduced graphene oxide (Co/N-CNTs@rGO) through a coordination-driven in situ self-assembly approach followed by pyrolysis. The integration of high intrinsic activity, enhanced conductivity, populated and richly exposed active species throughout the laminated hierarchical composite structure endows Co/N-CNTs@rGO with appealing bifunctional oxygen electrocatalysis properties. Impressively, Co/N-CNTs@rGO was subsequently fabricated as the air electrode in a rechargeable Zn−air battery, and the device achieves a maximum power density of 168 mW cm −2, a large specific capacity of 765 mA h g −1 while maintaining satisfying cycling durability. This work may provide valuable insights in regulating the coordination polymer derivatives and bring new perspectives for future design of promising composites electrocatalysts for electrochemical conversions and energy storage technologies. Graphical abstract: Image 1